Activity and Process Stability of Purified Green Pepper (Capsicum annuum) Pectin Methylesterase - Castro, Sónia Marília (2012)
Pectin methylesterase (PME) from green bell peppers (Capsicum annuum) was extracted and purified by affinity chromatography on a CNBr-Sepharose-PMEI column. A single protein peak with pectin methylesterase activity was observed. For the pepper PME, a biochemical characterization in terms of molar mass (MM), isoelectric points (pI), and kinetic parameters for activity and thermostability was performed. The optimum pH for PME activity at 22 °C was 7.5, and its optimum temperature at neutral pH was between 52.5 and 55.0 °C. The purified pepper PME required the presence of 0.13 M NaCl for optimum activity. Isothermal inactivation of purified pepper PME in 20 mM Tris buffer (pH 7.5) could be described by a fractional conversion model for lower temperatures (55?57 °C) and a biphasic model for higher temperatures (58?70 °C). The enzyme showed a stable behavior toward high-pressure/temperature treatments. Keywords: Capsicum annuum; pepper; pectin methylesterase; purification; characterization; thermal and high-pressure stability